Reconciling Religion and Law: The MUI Fatwa and the Constitutional Court’s Ruling on Children Born Out of Wedlock - Hidayatulloh, Haris (International Journal of Scientific Research and Management (IJSRM), 2025)
Article 100 of the Compilation of Islamic Law (KHI) and Article 43(1) of Law No. 1 of 1974 on Marriage state that a child born out of wedlock has civil relations only with the mother and her family. However, following the Constitutional Court Decision No. 46/PUU-VIII/2010, such a child is also deemed to have civil relations with the biological father, provided that a biological link is proven through science and technology and/or other legal evidence. This landmark ruling triggered public debate and controversy, notably from the Indonesian Ulema Council (Majelis Ulama Indonesia/MUI), which expressed concern that the decision could indirectly legitimize adultery. In response, MUI issued a firm fatwa asserting that a child born out of wedlock has no lineage (nasab), inheritance, guardianship (wali), or financial obligations (nafaqah) from the biological father, but only from the mother and her family. However, to ensure child protection, MUI mandates the father to provide for the child’s needs and issue a mandatory will (wasiat wajibah). This study uses a normative juridical method with a literature review approach and descriptive analysis. The fatwa represents a wise, innovative legal stance that upholds Islamic principles while promoting civil rights for the child within the framework of public welfare (maslahah).